Cryptosporidium and Giardia in Livestock in Tigray, Northern Ethiopia and Associated Risk Factors for Infection: A Cross-Sectional Study - Kifleyohannes, Tsegabirhan; Nødtvedt, Ane; Debenham, John James; Terefe, Getachew; Robertson, Lucy J. (Frontiers in Veterinary Science, 2022)
The occurrence and species/genotypes of Cryptosporidium and Giardia duodenalis infecting young livestock in selected districts of Tigray, Ethiopia were investigated, along with risk associated with infection. A total of 757 faecal samples were collected from calves, lambs, and goat kids from four rural districts in Tigray, and also from calves in periurban Mekelle, Tigray’s main city, and analysed for Cryptosporidium oocysts and Giardia cysts. Farmers answered questionnaires regarding potential risk factors at sample collection. Immunofluorescent antibody staining was used for parasite detection, and PCR at selected genes and sequencing of positive samples was used for molecular characterization. The occurrence of Cryptosporidium infection was 10%, 9%, and 4% in calves, lambs, and goat kids, respectively; equivalent figures for Giardia infection were 39%, 32%, and 21%. Molecular characterization of Cryptosporidium isolates revealed C. ubiquitum, subtype XIIa in all three species; C. ryanae in calves and goat kids; C. andersoni and C. bovis were identified only in calves, and C. xiaoi was identified in lambs. For Giardia, Assemblage E predominated in all host species, but among calf isolates we also identified a few potentially zoonotic genotypes (assemblages A (AI) and Assemblage B). Periparturient care was shown to be a particularly relevant risk factor for infection, and infections were less likely to occur under extensive management systems. Our major findings were widespread occurrence of both parasites in livestock, and the apparent lack of the most common zoonotic species. Our results are discussed in relation to other relevant studies, and we note that the effect of these common parasites on livestock productivity in this situation is important, given the dependency on healthy animals for the livelihoods of the population of Tigray.